Talking Together, Thinking Alone: Relations among Co-Rumination, Peer Relationships, and Rumination. - Felton, Julia W.; Cole, David A.; Havewala, Mazneen; Kurdziel, Gretchen; Brown, Victoria (Journal of Youth & Adolescence, 2019)
Girls are more likely to engage in rumination, associated with the development of mental health problems, as well as report higher levels of friendship quality, hypothesized to protect against these disorders. The current study examined whether co-rumination may drive simultaneous increases in rumination and changes in friendship quality among adolescents. The project included 360 participants (43% boys), ages 9.8 to 15.8 years, and analyses revealed that co-rumination mediated the link between female sex and both rumination and negative friendship quality. There was also a bidirectional relation between co-rumination and positive friendship quality. These findings highlight several pathways by which co-rumination mediates the relation between sex and both maladaptive (i.e. rumination, negative friendship quality) and adaptive (i.e. positive friendship quality) outcomes.